1977
DOI: 10.1203/00006450-197704000-01018
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Conventional Respiratory Monitoring to Detect Hypoxia

Abstract: Ris ens. arid W.G. Z l s t r a . From t h e x o m S t a t e -Un v e r s l t y ,-I-+-Gron ngen ~letlierlands(Spon. by M. Klaus) Recent reports Indicate t h a t both heat production and heat l o s s i n low birthweight Infants i n incubators exceed the "basal"values. This i s thought t o be a r e s u l t of non-optimal environriental conditions i n the Incubator. To study t h f s we measured both heat production and evaporative and non-evaporative heat l o s s simultaneously in r e s t i n g newborn Infants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1979
1979
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…'2 As episodes of apnoea that result in bradycardia start with a relatively low SaO2, one would also expect a greater reduction in SaO2 during an episode of bradycardia compared with an episode of apnoea not accompanied by bradycardia. We have shown this, but using a six seconds averaging time on our oximeter we were unable to study the temporal relationship between a fall in SaO2 and the onset of bradycardia as described by Henderson-Smart et al 3 They postulated that bradycardia was a peripheral chemoreflex response to falling SaO2. We feel, however, that one should be wary of ascribing cause and effect to this relationship, as bradycardia is more common when there is an obstructive element to the apnoea,'4 and episodes of apnoea with such an element may also be associated with a more pronounced reduction in SaO2.…”
Section: Alarm Limitsmentioning
confidence: 77%
“…'2 As episodes of apnoea that result in bradycardia start with a relatively low SaO2, one would also expect a greater reduction in SaO2 during an episode of bradycardia compared with an episode of apnoea not accompanied by bradycardia. We have shown this, but using a six seconds averaging time on our oximeter we were unable to study the temporal relationship between a fall in SaO2 and the onset of bradycardia as described by Henderson-Smart et al 3 They postulated that bradycardia was a peripheral chemoreflex response to falling SaO2. We feel, however, that one should be wary of ascribing cause and effect to this relationship, as bradycardia is more common when there is an obstructive element to the apnoea,'4 and episodes of apnoea with such an element may also be associated with a more pronounced reduction in SaO2.…”
Section: Alarm Limitsmentioning
confidence: 77%
“…Many of these studies defined apnea events from nursing charts, which have been demonstrated by us 13 and others 14,15 to underreport and inaccurately identify apnea events. The current study, as well as a report by Belal et al, 16 quantifies apnea events from a computer analysis of waveforms continuously collected from bedside monitors.…”
Section: Discussionmentioning
confidence: 99%
“…19 shows that baseline heart rate was not significantly different in infants with normoxemia and hypoxemia. PEABODY has reported that of 178 apnoeic episodes resulting in tcPo 2 less than 40 mm Hg, heart rate feil to below 100 beats/min in less than 60% and thoracic impedance alarms detected less than 40% [53]. Fig.…”
Section: The Newborn -Receiving Intensive Carementioning
confidence: 97%
“…More gradual changes in Po 2 due to increasing atelectasis, respiratory failure, development of sepsis, and development of chronic hing disease, can be assessed with more perspective by a continuou$ monitoring technique than by intermittent blood samples, Because of the intermittency of arterial blood gases and the complications of indwelling catheters or when an infant is too old, many physicians have attempted to rely on other means of cardiorespiratory monitoring, such äs heart rate and thoracic impedance, in between arterial Po 2 determinations. Cpntinuous tcPo 2 monitoring has repeatedly documented the problems with the use of heart rate and thoracic impedance äs indicators of oxygenation Status [37,39,48,53,54,57,60]. Fig.…”
Section: The Newborn -Receiving Intensive Carementioning
confidence: 99%